2010
DOI: 10.1002/jgm.1526
|View full text |Cite
|
Sign up to set email alerts
|

Improved transfection efficiency of an aliphatic lipid substituted 2 kDa polyethylenimine is attributed to enhanced nuclear association and uptake in rat bone marrow stromal cell

Abstract: Improved transfection efficiency of PEI2LA was attributed to enhanced association with the nucleus, which may be a result of hydrophobic interaction between the lipid moieties on the modified lipopolymer and the nuclear membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…The presence of 10% serum, which was avoided by most studies, may explain the greater size of polyplexes observed in this work. In one study, where the size measurements of PEI polyplexes were reported in 1% serum, the observed sizes (210-663 nm) were in line with the current study at similar DNA and polymer concentrations [32].…”
Section: Sizes Of Pei-peg Polyplexessupporting
confidence: 90%
See 3 more Smart Citations
“…The presence of 10% serum, which was avoided by most studies, may explain the greater size of polyplexes observed in this work. In one study, where the size measurements of PEI polyplexes were reported in 1% serum, the observed sizes (210-663 nm) were in line with the current study at similar DNA and polymer concentrations [32].…”
Section: Sizes Of Pei-peg Polyplexessupporting
confidence: 90%
“…The sources of all plasmids and tissue culture reagents were described previously [32]. SYBR Green I was purchased from Invitrogen (Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we investigated the efficiency of hydrophobe-substituted bPEI derivatives in the transfection of these cells. Different fatty acid-based substitutes have been investigated, namely stearic acid (St, C18 chain), linoleic acid (LA, C18:2 (6, 9) chain), and propionic acid (PrA, C3 chain), already reported to improve the transfection activity of bPEI on other cell types such as human embryonic kidney cells (293T) [17], rat bone marrow stromal cells (rBMSC) [25] and human breast cancer cells (MDA-231 and MCF-7) [19]. Besides, two new families of bPEI derivatives, carrying α-linoleic acid (αLA, C18:3 (3, 6, 9) chain) and acrylic acid (AcA, C3:1 (1) chain), were synthesised and studied, aiming to evaluate whether an increase in the level of unsaturation in the aliphatic chain of linoleoyl-and propionyl-based substitutes (i.e., an additional double bond, in position 3 and 1, respectively) could lead to a further enhancement in the transfection efficiency of bPEI derivatives on vascular cells.…”
Section: Resultsmentioning
confidence: 99%